2011
DOI: 10.1111/j.1365-2591.2011.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two Ni‐Ti systems and hand files for removing gutta‐percha from root canals

Abstract: The Ni-Ti systems were more effective and faster than hand files, although all techniques left gutta-percha and sealer remnants on the root canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 21 publications
8
86
0
14
Order By: Relevance
“…This fact is probably responsible for the several controversies existing among different studies, since root canal anatomy can influence the amount of remaining filling material after retreatment, irrespective of the technique used (BARRIESHI-NUSAR, 2002; GIULINI, COCHETTI; PAGAVINO, 2008;HAMMAD, QUALTROUGH, SILIKAS, 2008). Despite this, some investigations also showed that both retreatment techniques evaluated in this study are incapable to completely remove filling material from root canal walls (ZMENER, PAMEIJER;BANEGAS, 2006;HAMMAD, QUALTROUGH, SILIKAS, 2008;BARLETTA et al, 2008;SOMMA et al, 2008;PIRANI et al, 2009;MOLLO et al, 2012), corroborating our findings.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This fact is probably responsible for the several controversies existing among different studies, since root canal anatomy can influence the amount of remaining filling material after retreatment, irrespective of the technique used (BARRIESHI-NUSAR, 2002; GIULINI, COCHETTI; PAGAVINO, 2008;HAMMAD, QUALTROUGH, SILIKAS, 2008). Despite this, some investigations also showed that both retreatment techniques evaluated in this study are incapable to completely remove filling material from root canal walls (ZMENER, PAMEIJER;BANEGAS, 2006;HAMMAD, QUALTROUGH, SILIKAS, 2008;BARLETTA et al, 2008;SOMMA et al, 2008;PIRANI et al, 2009;MOLLO et al, 2012), corroborating our findings.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies on extrusion of root filling used methods in which the extruded material was freely released, without any barrier to block debris (IMURA et al, 2000;HUANG et al, 2007;SOMMA et al, 2008;MOLLO et al, 2012). This fact does not correspond to the clinical reality, because periodontal structures prevent larger amounts of debris to reach the apical region 1115 Micro-computed tomographic… AZEVEDO, K. C. M. et al (SELTZER et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Irregularities, isthmuses and recesses 4 hamper filling material removal, cleaning and preparation of the root canal, by providing a refuge for microorganisms 3 , and thus compromising the success of endodontic retreatment. In the present study, the selection of curved mesial roots of mandibular molars with isthmuses may explain the large amount of remaining filling material, as compared with other studies in the literature 10 . Most remaining filling material was found in the isthmus, in canal wall irregularities and in the apical third.…”
Section: Discussionmentioning
confidence: 71%
“…Most experimental studies comparing the efficacy of different techniques for retreatment were conducted using single straight root canals 5,8,10,11 , to simplify the standardization of specimens. Although teeth with complex anatomy represent a common clinical situation 23 , investigations of non-surgical retreatment techniques for teeth with 2 curved canals and an isthmus are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation